Distribution of matrimonial property upon dissolution of marriage: dual aspects of Muslim family law and adat customary law / Zakaria Ariffin - Ariffin, Zakaria (Faculty of Law, 1982)
The matrimonial relief provided for under the Muslim Law includes the distribution of Sepencarian Property. Under the introduction chapter of the paper we shall see the other matrimonial relief available to the spouses and we shall also see the confusion with regard to terminology of the word Harta Sepencarian and Harta Syarikat. In this respect it shall be seen that the confusion is not really with the terminology but rather under which legal system it applies. In Chapter Two of the paper we shall see a discussion of Sepencarian principle from the viewpoint of Adat Customary Law. Here we shall see the distribution under the Adat Perpateh as well as under the Adat Temenggong. It shall be noticed that Charian Laki Bini and Harta Sepencarian is not very much different from each other. As a matter of fact, Harta Sepencarian is said to be originating from Charian Laki Bini concept o In the third chapter, we shall discuss another set of principles on the same point from Islamic viewpoint. In this chapter we shall attempt to show its relevancy to our modern society and an explanation of a proposition of Law on that point. In the fourth chapter we shall discuss the present practices of Syariah Court relating to the distribution o From the interviews and reports of cases we shall see that the principle of distribution is not strictly followed by the Syariah Court, rather they would look at the facts of each and every case before making the distribution.